Annual cycles of diving behavior and ecology of the Weddell seal - Castellini, Michael Angelo; Davis, Randall William; Kooyman, Gerald L. (University of California Pres, 1992)
Bulletin of the Scripps Institution of Oceanography, La Jolla, California ; v. 28